Jurnalisme Damai dalam Pemberitaan Pembakaran Gereja di Aceh Singkil pada Harian Waspada - Raihan Nusyur (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
The burning church in Aceh Singkil on October 13, 2015 has caught the attention of local, national and even international media. The conflict motivated by the building permit issue required the media to expose the issue as it was. This study aims to get a picture of how Waspada Daily implemented peace journalism in reporting this case. The theory used in this research is peace journalism theory by Johan Galtung. The research used a quantitative approach with content analysis method towards 17 news articles published between 12 and 26 October 2015 which were selected based on purposive sampling techniques. Data were presented in the form of statistical frequency. The research findings show that the Waspada Daily news on the church burning in Aceh Singkil applied four categories of peace journalism by Johan Galtung and met all indicators in each category.